2014
DOI: 10.3324/haematol.2014.111740
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro sensitivity of blastic plasmacytoid dendritic cell neoplasm to SL-401, an interleukin-3 receptor targeted biologic agent

Abstract: ABSTRACTlabile group of amino acids to a diphtheria toxin (DT) payload that has been truncated at its receptor binding region. 20 Since IL-3, the natural ligand for IL-3R, binds with very high specificity and avidity, 21 SL-401 is able to transport DT efficiently and preferentially to cells that overexpress IL-3R, leading to internalization followed by receptor-mediated endocytosis and localization of SL-401 to early endosomes. After cleavage of the SL-401 DT constituent in the acidic medium of endosomes, DT t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 39 publications
3
38
0
Order By: Relevance
“…Specifically, we found that pDC-MM cell interactions significantly increases IL-3 secretion; and importantly, that IL-3 both stimulate pDC survival 9 and MM cell growth. 10 Our and other prior studies showed that pDCs, including MM patient pDCs, highly express IL-3 R. 5,1113 These findings demonstrate functional significance of IL-3 R-mediated signaling during pDC-MM interactions, and provide the rationale for therapeutically targeting IL-3 R-positive pDCs in MM.…”
Section: Introductionsupporting
confidence: 53%
“…Specifically, we found that pDC-MM cell interactions significantly increases IL-3 secretion; and importantly, that IL-3 both stimulate pDC survival 9 and MM cell growth. 10 Our and other prior studies showed that pDCs, including MM patient pDCs, highly express IL-3 R. 5,1113 These findings demonstrate functional significance of IL-3 R-mediated signaling during pDC-MM interactions, and provide the rationale for therapeutically targeting IL-3 R-positive pDCs in MM.…”
Section: Introductionsupporting
confidence: 53%
“…This led to the development of SL-401 an IL-3-diphtheria toxin conjugate that has demonstrated promise for BPCDN in early-phase trials. [61][62][63]65 Thus, a variety of prospective phase trials are greatly needed to unravel the many questions that persist in the treatment of this aggressive and elusive neoplasm.…”
Section: Resultsmentioning
confidence: 99%
“…Cytotoxicity is mediated by the catalytic domain after processing through the endosome, which inactivates protein synthesis by adenosine 59-diphosphate-ribosylating a diphthamide residue in elongation factor 2, resulting in cell lysis or apoptosis. Angelot-Delettra et al 61 demonstrated that SL-401 decreased viability in 75% of BPDCN primary cells compared with a 13% decrease in ALL and a 26% decrease in AML cells. The degree of cell killing was inversely proportional to the expression of the IL-3Ra chain (CD123) but not the IL-3Rb chain (CD131).…”
Section: Novel Therapymentioning
confidence: 99%
“…Therapeutic strategies of BPDCN propose to interfere with IL-3 2,16,34,46 because BPDCNs express high levels of CD123, 2,26 and IL-3 is a BPDCN survival factor. 1,15 Here, we explored how LXR activation and LXR-induced cholesterol efflux interact with this pathway.…”
Section: Discussionmentioning
confidence: 99%